Mechanical, thermal, and morphological properties of low-density polyethylene nanocomposites reinforced with montmorillonite: Fabrication and characterizations. Issue 1 (31st December 2023) - Al-Jumaili, Safaa Kh.; Alkaron, Wasan A.; Atshan, Maithem Y.
Abstract: Nanoparticle incorporation in polymeric matrices to generate polymer nanocomposite with the intention of maximizing the "nano-effect" derived from the nanoparticles and minimizing the drawbacks of the polymer is an emerging field of research. In this study, low-density polyethylene (LDPE) was mixed with varying concentrations of montmorillonite (MMT) nanoclays to create a polymer nanocomposite with desirable characteristics. Composite sheets with nanoclays contents of (0, 1, 2, 3, and 4 wt%) were prepared for hardness, tensile-fractography, thermal conductivity, and tensile testing (elongation and stress-at-break). The results showed that, according to scanning electron microscope (SEM) study, LDPE has a low flexibility temperature and is prone to corrosion. For larger MMT filler loadings (>3% wt), tensile-fractography showed nanoclays particle micro-aggregation. The pure LDPE sample fracture's tensile-fractography showed plastic deformation. MMT/LDPE samples with 3% wt hard MMT filler have brittle fractures without appreciable plastic deformation. Thermal conductivity test results show that LDPE/MMT composite thermal conductivity decreased with increasing clay concentration. The thermal conductivity values were reduced from a value of 0.13 W/m.K to a value of 0.039 W/m.K when reinforced with 0% wt to 3% wt filler loading, respectively. With 4% wt filler loading, LDPE/MMT composites had the highest shore hardness at 47.4. Yet, tensile tests indicated that increasing clay content improved the composite's characteristics. At modest loading percentages (1–2 wt%), tensile results were excellent. Furthermore, the elongation at break of the unadulterated LDPE was reduced by 20% and 30% after introducing 1% wt and 2% wt of MMT as reinforcement additives, respectively. Hence, MMT clay can improve the mechanical properties and thermal insulation of LDPE polymer matrix.